Upaya Preventif Keselamatan Perlintasan Sebidang Pada JPL 210 Bojonegoro Melalui Kampanye Edukasi Visual - Apriliani, Nurul Fitria; Prihatanto, Rusman; Leliana, Arinda; Puspitasari, Armyta (SOROT : Jurnal Pengabdian Kepada Masyarakat, 2026)
Level crossings are recognized as high-risk locations for traffic accidents and therefore require focused attention, particularly in the context of early preventive measures. This community service program aimed to enhance public awareness of compliance with traffic regulations at level crossings and to improve road users’ vigilance as a preventive effort to reduce accident risk at the JPL 210 level crossing in Bojonegoro. The program was implemented through a safety awareness campaign involving the distribution of visual educational materials in the form of leaflets and the installation of safety message banners in the vicinity of the crossing. The results indicate that the safety campaign utilizing leaflets and banners was effective in attracting the attention of road users. Road users demonstrated positive responses, as evidenced by their willingness to receive and read the leaflets, as well as increased caution when approaching and crossing the railway line. Based on observational data from 30 road users collected before and after the implementation of the safety campaign at the JPL 210 level crossing, a significant improvement in compliance levels was observed. The average compliance rate increased from 55.71% prior to the safety campaign to 76.18% following its implementation. The most notable improvements were observed in indicators related to speed reduction and the practice of looking both left and right before crossing